Dynamic functional networks in idiopathic normal pressure hydrocephalus: Alterations and reversibility by CSF tap test. Issue 5 (9th December 2020) - Griffa, Alessandra; Bommarito, Giulia; Assal, Frédéric; Herrmann, François R.; Van De Ville, Dimitri; Allali, Gilles
Abstract: Idiopathic Normal Pressure Hydrocephalus (iNPH)—the leading cause of reversible dementia in aging—is characterized by ventriculomegaly and gait, cognitive and urinary impairments. Despite its high prevalence estimated at 6% among the elderlies, iNPH remains underdiagnosed and undertreated due to the lack of iNPH‐specific diagnostic markers and limited understanding of pathophysiological mechanisms. INPH diagnosis is also complicated by the frequent occurrence of comorbidities, the most common one being Alzheimer's disease (AD). Here we investigate the resting‐state functional magnetic resonance imaging dynamics of 26 iNPH patients before and after a CSF tap test, and of 48 normal older adults. Alzheimer's pathology was evaluated by CSF biomarkers. We show that the interactions between the default mode, and the executive‐control, salience and attention networks are impaired in iNPH, explain gait and executive disturbances in patients, and are not driven by AD‐pathology. In particular, AD molecular biomarkers are associated with functional changes distinct from iNPH functional alterations. Finally, we demonstrate a partial normalization of brain dynamics 24 hr after a CSF tap test, indicating functional plasticity mechanisms. We conclude that functional changes involving the default mode cross‐network interactions reflect iNPH pathophysiological mechanisms and track treatment response, possibly contributing to iNPH differential diagnosis and better clinical management. Abstract : Idiopathic normal pressure hydrocephalus (iNPH), the leading cause of reversible dementia in ageing, is a prevalent neurological disorder characterised by gait, urinary, and cognitive impairments with ventriculomegaly. We show that iNPH patients have changes of brain functional dynamics which explain gait and executive deficits, are partially reverted by a CSF tap test, and are not driven by Alzheimer's disease or cerebrovascular comorbidities. Our results shed new light on the neurobiological substrates of iNPH and functional plasticity mechanisms following an invasive intervention, with possible implications for iNPH differential diagnosis and better clinical management.